O cantar de amigo galego-português : notas sobre um estudo recente - Miranda, José Carlos Ribeiro (2000)
After more than a century of an 'official doctrine on the cantigas de amigo' at university level, recent works, such as Maria do Rosário Ferreira's 'Aguas Doces, Águas Salgadas', establish the basis of a methodologically updated approach which can also be shared by the various disciplines interested in this literary domain.